Productivity of peanut at abandoned pumice mining land in West Nusa Tenggara, Indonesia - Suriadi, A; Zulhaedar, F; Wirajaswadi, L (Journal of Degraded and Mining Lands Management, 2014)
Four packages of peanut technologies, PTB1 (soil tillage, certified seed, dibbling with 40cmx10cm and 2 seeds/hole, seeds treatment, fertilizer 200 kg/ha Phonska (NPK fertilizer), and pests control with IPM methods), PTB2 (similar to PTB1 except for no seed treatment and fertilizer of urea for 50 and SP36 for 100 kg/ha), PTB3 (similar to PTB2 except for 40x15cm spacing and fertilizer of urea 50 kg/ha), and PTP (famer practice, uncertified seeds, irregular spacing, no seed treatment, no fertilizer, and no pest control) were examined the agronomic adaptability and economy value in pumice stone mining land at the Akar-akar Village of North Lombok District. Each package that was applied on an area of 0.5 ha was repeated three times at different farmers group. Economic analysis was performed to obtain revenue over variable costs (RAVC) and marginal benefit cost ratio (MBCR). The results showed that the highest fresh pod yield (4.50 t/ha) and the highest dry pod yields (2.30 t/ha) were observed for PTB1. These values, however, did not significantly different from those of other PTP treatments. The lowest fresh and dry pod yields were observed for at PTP treatment and these were significantly different from all PTB treatments. The highest of net income of farmers from the application of package of technologies was obtained from the PTB1 (Rp 8.970.00), while the highest MBCR value was obtained from the PTB3 (5.51). This indicated that the PTB3 was the promising peanut package of technology that may be applied on abandoned pumice stone mining land.